The Existence of Mothers Using Social Media in Families in Sincimun Village East Halongonan District - Wulandari, Mira; Mirzaya Putra, Ilham (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: This study aims to explore the effects of social media usage by housewives in Siancimun Village, Halongonan Timur District, on family harmony. As social media usage increases across various segments of society, this phenomenon has begun to influence family life, particularly among housewives who play a dominant role in household dynamics. Methodology: This research employs a descriptive qualitative approach, utilizing data collection methods such as observation, interviews, and documentation. The data analysis method used in this study includes data reduction, data presentation, and data verification in order to draw conclusions. The validity of qualitative research data was tested using credibility, transferability, dependability, and confirmability techniques. Main Findings: The findings of the study indicate that social media offers various benefits, such as facilitating communication, providing access to information, and serving as a source of inspiration for housewives in Siancimun Village. However, uncontrolled usage may lead to negative consequences, including reduced productivity, family conflicts, and imbalances in household roles. Therefore, awareness and wise time management are essential to ensure that social media is used positively without disrupting family harmony. Novelty/Originality of this study: This study contributes to addressing the research gap concerning the use of social media by housewives in rural areas, specifically in Siancimun Village, Halongonan Timur District. Previous studies have generally discussed the impact of social media on society at large, highlighting both its positive aspects, such as facilitating communication, and its negative aspects, such as fostering dependency.